ANALISIS TINGKAT PELAYANAN JALAN BERDASARKAN DERAJAT KEJENUHAN PADA PERTIGAAN AYAM GEPREK KAMPUNG PEKAT MENGGUNAKAN METODE MKJI 1997 - hermansyah -; Septiani; Putrianti; Laila Riskiani; Ilham Maulana; Ozzy Maulana (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2026)
Evaluating the operational performance of an intersection is essential to determine its ability to accommodate traffic flow effectively. This study analyzes the level of service based on the degree of saturation at the threeleg Ayam Geprek Kampung Pekat intersection using the Indonesian Highway Capacity Manual (MKJI 1997). Traffic data were collected manually at 15-minute intervals and classified into motorcycles, light vehicles, and heavy vehicles, then converted into hourly volumes and expressed in Passenger Car Units (PCU). The analysis included identifying the peak hour, determining traffic flow, estimating capacity, and calculating the degree of saturation as the main indicator of performance. The results show that the degree of saturation reached 0.66 on Friday and 0.57 on Saturday, both falling within the Level of Service (LOS) C category. These values indicate that the intersection operates under stable conditions, although maneuvering space begins to decrease, particularly on Friday when the DS value is relatively higher. Differences between the two observation days reflect variations in traffic activity but do not significantly affect the overall flow. The findings provide an empirical overview of the intersection’s performance and can serve as a reference for future traffic planning and management in areas with similar characteristics